2009
DOI: 10.1007/s11085-009-9171-0
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxidation at Low Temperature (260–500 °C) in Air and the Effect of Water Vapor

Abstract: The oxidation of iron has been studied at low temperatures (between 260 and 500°C) in dry air or air with 2 vol% H 2 O, in the framework of research on dry corrosion of nuclear waste containers during long-term interim storage. Pure iron is regarded as a model material for low-alloyed steel. Oxidation tests were performed in a thermobalance (up to 250 h) or in a laboratory furnace (up to 1000 h). The oxide scales formed were characterized using SEM-EDX, TEM, XRD, SIMS and EBSD techniques. The parabolic rate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 40 publications
7
43
0
1
Order By: Relevance
“…1) that corresponds to alloy oxidation. The thermogravimetric curves were treated using a method after Monceau and Pierragi [16,17]. For all tested conditions, the mass gain increased reaching a quasi-stationary regime after a transitory period shorter than 125 h. This result is illustrated for the test 8 in Fig.…”
Section: Isothermal Thermogravimetrymentioning
confidence: 65%
“…1) that corresponds to alloy oxidation. The thermogravimetric curves were treated using a method after Monceau and Pierragi [16,17]. For all tested conditions, the mass gain increased reaching a quasi-stationary regime after a transitory period shorter than 125 h. This result is illustrated for the test 8 in Fig.…”
Section: Isothermal Thermogravimetrymentioning
confidence: 65%
“…At 300 °C, a change in the oxidation rate and the dominant oxide begins [28,29]. The formation of Fe 2 O 3 with increasing temperatures, from 300 °C, has been reported to be accompanied by oxide separation from the metal surface [28,29]. These oxides were observed to occur predominately within the grinding grooves of the steel.…”
Section: Effect Of Surface Oxidationmentioning
confidence: 99%
“…Fe 3 O 4 is reported as the dominant oxide at 200 °C, and has been observed to have good oxide adherence with the steel substrate [27,28]. At 300 °C, a change in the oxidation rate and the dominant oxide begins [28,29]. The formation of Fe 2 O 3 with increasing temperatures, from 300 °C, has been reported to be accompanied by oxide separation from the metal surface [28,29].…”
Section: Effect Of Surface Oxidationmentioning
confidence: 99%
“…23). Indeed, as hematite often crystallizes to whiskers shapes [17] and as hematite powder is known to be red-whereas thick hematite layer is black-the oxide whiskers were assumed to be hematite as well. When hematite was formed without any whiskers morphology (typically in the center of the specimen), it was observed that the colour was rather dark grey.…”
Section: Morphology Of the Corrosion Layersmentioning
confidence: 99%